Quantitative Analysis of Carbon Steel with Multi-Line Internal Standard Calibration Method Using Laser-Induced Breakdown Spectroscopy. Issue 4 (April 2016) - Pan, Congyuan; Du, Xuewei; An, Ning; Zeng, Qiang; Wang, Shengbo; Wang, Qiuping
A multi-line internal standard calibration method is proposed for the quantitative analysis of carbon steel using laser-induced breakdown spectroscopy (LIBS). A procedure based on the method was adopted to select the best calibration curves and the corresponding emission lines pairs automatically. Laser-induced breakdown spectroscopy experiments with carbon steel samples were performed, and C, Cr, and Mn were analyzed via the proposed method. Calibration curves of these elements were constructed via a traditional single line internal standard calibration method and a multi-line internal standard calibration method. The calibration curves obtained were evaluated with the determination coefficient, the root mean square error of cross-validation, and the average relative error of cross-validation. All of the parameters were improved significantly with the proposed method. The results show that accurate and stable calibration curves can be obtained efficiently via the multi-line internal standard calibration method.